2018
DOI: 10.3390/coatings8040145
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Laser Microtexturing on the Wetting Behavior of Ti6Al4V Alloy

Abstract: Surface modification procedures by laser techniques allow the generation of specific topographies and microstructures that enable the adaptation of the external layers of materials for specific applications. In laser texturing processes, it is possible to maintain control over the microgeometry and dimensions of the surface pattern through varying the processing parameters. One of the main areas of interest in the field of surface modification treatments is the ability to generate topographies that are associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 33 publications
(43 reference statements)
3
9
0
Order By: Relevance
“…When V s was increased, an important growth occurred on the contact angle values, raising the hydrophobic behavior trends of the modified surface. This is especially caused by an increase in the compactness of the treated layer as a result of the development of textures with a higher contact area between different phases [19]. This phenomenon is reproduced under all the range of E d analyzed in this work.…”
Section: Friction Coefficient Of the Tested Surfaces Under Wet Conditsupporting
confidence: 55%
See 4 more Smart Citations
“…When V s was increased, an important growth occurred on the contact angle values, raising the hydrophobic behavior trends of the modified surface. This is especially caused by an increase in the compactness of the treated layer as a result of the development of textures with a higher contact area between different phases [19]. This phenomenon is reproduced under all the range of E d analyzed in this work.…”
Section: Friction Coefficient Of the Tested Surfaces Under Wet Conditsupporting
confidence: 55%
“…Wear volume is not just affected by the wettability of the texture, but also by V s parameter. This control parameter was related to the thermochemical process that produced the oxidation of the surfaces, the possible changes produced on the microstructure of the layer and the thickness of the affected layer [15,19,36]. This fact confirmed that laser surface processing results in a protective mechanism of the Ti6Al4V against tribological wear effects.…”
Section: Wear Behavior Of Modified Surfacessupporting
confidence: 53%
See 3 more Smart Citations